The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2020
DOI: 10.3389/fonc.2020.00710
|View full text |Cite
|
Sign up to set email alerts
|

Sucralose Promotes Colitis-Associated Colorectal Cancer Risk in a Murine Model Along With Changes in Microbiota

Abstract: Sucralose is a calorie-free high-intensity artificial sweetener that is widely used in thousands of foods and beverages all over the world. Although it was initially regarded as a safe, inert food additive, its adverse effect on gut microbiota and health has drawn more and more attention as evidence accumulates. Studies by us and others revealed that sucralose exacerbated gut damage and inflammation in animal models for inflammatory bowel disease (IBD), including those for both ulcerative colitis, and Crohn's … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
29
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(34 citation statements)
references
References 46 publications
(59 reference statements)
2
29
0
3
Order By: Relevance
“…Regarding sucralose, though it is considered harmless and without the genotoxic potential to produce genetic damage or cancer in humans, a study mentioned that because of the conditions that this sweetener causes on the intestine (the inactivation of digestive proteases, the microbiota, and the intestinal barrier), it can promote the development of colorectal cancer [ 80 ].…”
Section: Resultsmentioning
confidence: 99%
“…Regarding sucralose, though it is considered harmless and without the genotoxic potential to produce genetic damage or cancer in humans, a study mentioned that because of the conditions that this sweetener causes on the intestine (the inactivation of digestive proteases, the microbiota, and the intestinal barrier), it can promote the development of colorectal cancer [ 80 ].…”
Section: Resultsmentioning
confidence: 99%
“…Other sucralose-containing commercial products, such as Sweetal (sucralose + sorbitol), significantly elevated liver enzyme levels (ALT, AST) and kidney function enzymes (urea, creatinine) in Balb/c albino mice after 18 weeks (administered 5 h/day in drinking water; 5.2 mg/ml sucralose) (2). Similar in vivo pro-inflammatory effects [hepatic mediators (5), severity of chemically-induced colitis (6, 57)] following pure sucralose supplementation have also been reported (5,6,57).…”
Section: Artificial Sweeteners On Digestive Inflammation Outcomesmentioning
confidence: 62%
“…While the Food and Drug Administration (FDA) deems AS to be safe, there is evidence that AS influence inflammation pathways (1)(2)(3)(4)(5)(6)(7). Owing to the potent sweetening effect of most AS and bitterness/lingering aftertaste, most commercial products contain a commercial proprietary blend of two or more AS, as well as ingredients to make AS more palatable.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…One of them is sucralose, which is used in wide variety of foods and beverages all over the world. Despite the fact that sucralose have been considered healthy, independent studies have shown that sucralose promotes gut damage, inflammation and colitis-associated CRC in murine models along with dysbiosis of gut microbiota [ 36 ].…”
Section: Colorectal Cancer—an Overviewmentioning
confidence: 99%